Cytotoxic prenylated indole alkaloid produced by the endophytic fungus Aspergillus terreus P63 - Gubiani, Juliana R.; Oliveira, Michele C. S.; Neponuceno, Ricardo A. R.; Camargo, Maria J.; Garcez, Walmir S.; Biz, Andressa R.; Soares, Marcos A.; Araujo, Angela R. [UNESP]; Bolzani, Vanderlan da S. [UNESP]; Lisboa, Helen C. F.; Sousa Jr, Paulo T. de; Vasconcelos, Leonardo G. de; et al. (Elsevier B.V., 2019)
Prenyl indole alkaloids constitute a diverse class of natural products with complex chemical structures and potent biological activities. Investigation of the growth medium EtOAc extract produced by the endophytic fungus Aspergillus terreus P63 collected from roots of the grass Axonopus leptostachyus, yielded the prenylated indole alkaloid, giluterrin, bearing an unprecedented carbon skeleton. The structure of giluterrin was established by analysis of spectroscopic data and HRMS. The absolute configuration of giluterrin was determined by combination of electronic and vibrational circular dichroism analyses. Giluterrin presented antiproliferative profile for prostate (PC-3) and kidney (786-0) cancer cell lines.
Keywords: Prenylated indole alkaloid; Fungal alkaloid; Endophytic fungus; Aspergillus terreus